Violência doméstica e familiar contra mulher e atuação da defensoria pública do Pará: a defesa e assistência interdisciplinar ao “homem agressor” pelo NEAH – símbolo ou política pública de prevenção de delitos - BASTOS, Alexandre Martins (Universidade Federal do Pará, 2019)
The present study has as its objective the analysis of the Maria da Penha Law, in the implementation of public policy at Core Specialized Customer Service Man (NEAH) the Public Defender’s Office. To that end it was necessary to check whether the NEAH has contributed to the prevention of domestic violence and family crimes in the city of Bethlehem, as well as assess the potential of the Core in constructing public policies, from their activities, through the reflection and therapeutic groups, or from the analysis of the communicative system in vision of Niklas Luhmann. Also, verify that public policy developed by NEAH translates into a symbol in the concept of Marcelo Neves or effective public policy. From the concepts acquired during the bibliographical study, suggested a new systemic conceptualization of binary code analysis for public defender (assistance-not assistance). The study developed as an exploratory research with qualitative approach, having the researcher based on systemic methodology of Niklas Luhmann, through participant observation. Primary data collection was performed by means of semi-structured interviews applied to assisted participants in focus groups and therapeutic of 2014, 2015 and 2016 the NEAH, and servers and public defender, booked at the Core. Even in data collection, documentary analysis of management would manage the NEAH from 2010 to 2016. The examination of the data occurred through content analysis, with the development of central and selective categorization encodings. The results made it possible to reveal that is symbolic to Edition of the Maria da Penha Law under two aspects analysed in the present research, and that the actions of the NEAH corresponded to a public policy effective in the pacification of the conflict and the construction of public policies. And finally, for the purpose of systemic communication, it appearsu that the core is a reflex assisted demand attitude